2021
DOI: 10.1097/ijg.0000000000001858
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Head Vessel Density Assessment in Recovered COVID-19 Patients: A Prospective Study Using Optical Coherence Tomography Angiography

Abstract: Precis: Vascular diseases have been linked to alterations in optic nerve head perfusion. Purpose: The main objective was to investigate the changes in peripapillary vessel density (VD) in post coronavirus disease (COVID-19) patients. Methods: In this prospective pilot exploratory study, patients with COVID-19 that were attended in the Emergency Department of Hospital Clinico San Carlos (Madrid) were included. All patients underwent optic nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…0.05, not shown). Regarding patients' medical history data, DM was associated with VD and RNFL (as in previous study, not shown) (9).…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…0.05, not shown). Regarding patients' medical history data, DM was associated with VD and RNFL (as in previous study, not shown) (9).…”
Section: Resultssupporting
confidence: 63%
“…No correlation was noted between VD, FI, or RNFL thickness at the 12-month visit and SARS-CoV-2 parameters, which included clinical parameters, disease severity, and blood test (all P > 0.05, not shown). Regarding patients' medical history data, DM was associated with VD and RNFL (as in previous study, not shown) (9).…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…Patients with COVID-19 were not assessed during the acute phase of the disease during hospitalization, and the healthy control group was relatively small. In addition, the study did not include patients with severe illness, some of whom may have died of the disease [ 28 ].…”
Section: Discussionmentioning
confidence: 99%